LncRNA LBX2-AS1 impacts osteosarcoma sensitivity to JQ-1 by sequestering miR-597-3p away from BRD4 - Li, Jiayu; Yuan, Xuhui; Ma, Cong; Li, Junhong; Qu, Gaoyang; Yu, Bo; Cai, Feng; Peng, Yuanxiang; Liu, Lang; Zeng, Duo; Jiao, QuanHui; Zhang, Jiongfeng; et al. (Frontiers in Oncology, 2023)
Objective: Recent knowledge concerning the significance of long non-coding RNA (lncRNA)-mediated ceRNA networks provides new insight into their possible roles as specific biomarkers for the treatment of osteosarcoma (OS). Thus, this study aims to clarify the functional relevance and mechanistic actions of lncRNA LBX2-AS1 in OS. Methods: Differential analysis was performed by integrating the TCGA and GTEx databases. Cox regression analysis was then employed to assess the prognostic value of the model. The expression of lncRNA LBX2-AS1 and miR-597-3p was quantified in OS cell lines by qRT-PCR. The proliferation, migration, invasion, and apoptosis of OS cell lines in response to manipulated lncRNA LBX2-AS1 were evaluated by MTT, colony formation, transwell, Western blot, and flow cytometry assays. Luciferase activity was assayed to validate the reciprocal regulation between lncRNA LBX2-AS1 and miR-597-3p. The protein levels of BRD4 and EMT-related factors were examined by Western blot assay. Finally, tumor growth in response to LBX2-AS1 knockdown was evaluated in xenograft-bearing nude mice. Results: By integrating the GTEx and TCGA databases, we identified 153 differentially expressed lncRNAs. Among them, 5 lncRNAs, RP11-535M15.1, AC002398.12, RP3-355L5.4, LBX2-AS1, and RP11.47A8.5, were selected to establish a model, which predicted the prognosis of OS. Higher lncRNA LBX2-AS1 expression was noted in OS tissues relative to that in normal tissues. Silencing lncRNA LBX2-AS1 faciliated apoptosis and curtailed proliferative, migratory, and invasive capacities of OS cells. Mechanistically, lncRNA LBX2-AS1 could elevate the expression of BRD4, an oncogene, by competitively binding to miR-597-3p. More importantly, knockdown of lncRNA LBX2-AS1 increased the sensitivity of OS cells to the BRD4 inhibitor JQ-1. Finally, the tumor growth of OS cell xenografts was constrained in vivo in the presence of lncRNA LBX2-AS1 knockdown. Conclusion: In conclusion, lncRNA LBX2-AS1 promotes the growth of OS and represses the sensitivity to JQ-1 by sponging miR-597-3p to elevate the expression of BRD4.